Hypocalcemia and Anemia in Pregnancy: A Hospital Based Study in Jumla, Nepal - Shah, Tirtha Narayan; Gurung, Sonam; Koirala, Sagar (Medical Journal of Eastern Nepal, 2024)
Background Hypocalcemia is a condition where the serum calcium is below the optimum level. Calcium supplements demand increases in pregnancy. Some complications of pregnancy may be associated with lower serum calcium level e.g. pre-eclampsia during pregnancy, low birth weight, preterm delivery, and neonatal death. Iron deficiency in pregnant women is a cause of anemia and predisposes women to urinary tract infections, low birth weight of newborns and a higher risk of premature birth. Methods This is an observational, descriptive, prospective study which was done after the IRC approval. Blood samples were obtained from the pregnant women in their routine antenatal check-up and serum total calcium and hemoglobin were estimated by O – Cresolphthalein Complexone (OCPC) method and Cyanmethemoglobin method respectively. Initially the data were recorded in MS-Excel 2007 and analyzed by SPSS16. Level of significance was defined at p<0.05 at 95% confidence interval. Results There were 280 participants in this study with age varying from 19 to 40 and the median age was 24 years. 68.2% of it had hypocalcemia and 11.8% had anemia. Conclusions Hypocalcemia and anemia alone or together is a severe condition during pregnancy. Enhancing dietary calcium and iron intake together with knowledge and awareness during pregnancy could mitigate the high prevalence of hypocalcemia and anemia, thereby improving maternal and fetal outcomes.